Impact Analysis of the Large-Scale Social Restrictions (PSBB) Policy Implementation in Jakart - Hikmahwati, Hikmahwati; Sangadji, Ekasafitri A.S; Utami, Raden Roro Mega (UI Scholars Hub, 2020)
Jakarta is the province with the highest population density in Indonesia and is also one of the main international gateways to enter Indonesia. These conditions cause a high risk of transmission COVID-19 in Jakarta. One of the government's decisions was applying the Large Scale Social Restrictions (PSBB) policy in Jakarta. This study is a documentation study with Sabatier and Mazmanian's top-down approach that aims to analyze the extent impact of policy implementation, in terms of the policy objectives and community compliance. Compliance analysis uses the results of the Covid-19 Outbreak Survey and Google mobility index. The result shows the compliance of the community in policy implementation. The impact of the PSBB implementation can be seen from the value of the Reproduction number (Rt), which has decreased since the PSBB policy was implemented. Based on those data, it can be concluded that the implementation of the PSBB in Jakarta has been going and implemented well; thus, the consistency from the community and also local government needs to be well maintained.